Study on the Application of Fit-Viability Framework for Renewable Energy Technology Evaluation - Azim, Arshad; Hassan, Ibrahim; Shahrani, Anuar; Ahmmad Shukrie, Md Yudin (2014)
Malaysia has an abundance of renewable energy resources. However, the implementation proved to be difficult, as many factors have to be considered, mainly economical factor. Furthermore, currently there is no known framework to establish the feasibility study of renewable energy technology implementation. This paper serves as an initial study on the application of fitviability framework for the implementation of RE technology, focussing in Malaysia. A simple case study has been performed based on the Feed-in Tariff mechanism, an the fit-viability framework proved to be useful in RE technology consideration.